A THEORETICAL AND APPLIED STUDY OF THE NATIONAL JUDICIAL REFORM - Яновська, О.Г (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2016)
In the review of the monograph “Theory and Practice of Judicial Reform in Ukraine” by Associate Professor O. Khotynska-Nor, the author praises the scientific novelty and thoroughness of the study. The reviewers emphasize that the monograph substantiates the need for a comprehensive concept of judicial reform based on the development of the rule of law and civil society in Ukraine, the ratification of the Convention for the Protection of Human Rights (1997) and recent changes to the Constitution and legislation on the judiciary. The author applies an integral interdisciplinary approach, combining sociology, economics, political science, philosophy and psychology, which allows us to consider judicial reform as an open social system dependent on the political, economic and socio-cultural environment. Particular attention is paid to the methodological foundations of the reform and the case law of the European Court of Human Rights as a source of transformational vectors for the national judicial system. The structure of the monograph consists of four logically interrelated sections: Theoretical and legal foundations of judicial reform - analysis of the state of scientific research, conceptual and categorical apparatus, subjects and principles of reform; Historical Stages of Judicial Development in Ukraine - an overview of the changing models of court organization, noting the chaotic nature of reforms and the need for a doctrinal framework; The impact of the ECHR case law on the national judicial system - comparative legal analysis, forecasting the directions of transformation; The role of judicial reform in the development of civil society - the importance of changes for guaranteeing fair justice and protecting human rights. The monograph is distinguished by a clear logic of presentation, a rich empirical base (statistical data) and specific proposals for improving legislation. It is intended for scholars, teachers, representatives of the judiciary and law enforcement agencies, attorneys, and all those involved in reforming the judiciary. The study is timely, meets modern challenges, and may become a doctrinal foundation for further transformations in the national judicial system.

У рецензії на монографію к. ю. н., доцента О. З. Хотинської-Нор «Теорія і практика судової реформи в Україні» висловлено високу оцінку наукової новизни та ґрунтовності дослідження. Рецензенти підкреслюють, що монографія обґрунтовує потребу в комплексній концепції реформи судової влади, виходячи з розвитку в Україні ідей правової держави й громадянського суспільства, ратифікації Конвенції про захист прав людини (1997) та останніх змін у Конституції й законодавстві про судоустрій. Авторка застосовує інтегральний міждисциплінарний підхід, поєднуючи соціологію, економіку, політологію, філософію та психологію, що дає змогу розглядати судову реформу як відкриту соціальну систему, залежну від політичного, економічного й соціокультурного середовища. Особлива увага приділена методологічним засадам реформи й практиці Європейського суду з прав людини як джерелу трансформаційних векторів для вітчизняної судової системи. Структура монографії складається з чотирьох логічно пов’язаних розділів: Теоретико-правові засади судової реформи — аналіз стану наукових досліджень, понятійно-категорійний апарат, суб’єкти й принципи реформи; Історичні етапи розвитку судової влади в Україні — огляд змінних моделей організації судів, відзначення хаотичності реформ і потреби в доктринальній основі; Вплив практики ЄСПЛ на вітчизняну судову систему — порівняльно-правовий аналіз, прогнозування напрямів трансформацій; Роль судової реформи в розвитку громадянського суспільства — значення змін для гарантування справедливого правосуддя та захисту прав людини. Монографія вирізняється чіткою логікою викладу, багатою емпіричною базою (статистичними даними) і конкретними пропозиціями щодо вдосконалення законодавства. Вона призначена для науковців, викладачів, представників судових і правоохоронних органів, адвокатів та всіх, хто займається реформуванням судової влади. Дослідження є своєчасним, відповідає сучасним викликам, може стати доктринальним фундаментом подальших перетворень у вітчизняній судовій системі.
ТЕОРЕТИКО-ПРИКЛАДНЕ ДОСЛІДЖЕННЯ ВІТЧИЗНЯНОЇ СУДОВОЇ РЕФОРМИ